INTEGRATING GREEN BUILDING PRINCIPLES AND ISLAMIC JURISPRUDENCE (FIQH) IN ABLUTION WASTEWATER REUSE FOR URBAN MOSQUES IN INDONESIA - Risma, Ulfiatun; Perwita Sari, Dany (Border: Jurnal Arsitektur, 2025)
In Indonesia, which is the most populous Muslim-majority country in the world, there is currently a shortage of water sources and mosques are considered as one of the public building that produce water waste the most because of the ablution (wudhu) activities. A medium-sized mosque, for instance, consumes water between 3,000 and 3,500 liters daily. Therefore, this study is aimed at incorporating green building and fiqh in the reuse of ablution wastewater. Using a qualitative-descriptive method, this study investigates the water use behavior, technology of water taps, and treatment feasibility for the study of mosque typologies. Wastewater from ablution is considered light greywater and is in a safe range of pollutants (TSS 0 mg/L, BOD 2.3 mg/L, COD 7.4 mg/L, pH 8.4) which meets the requirements of class I clean water. Multi-stage sedimentation, sand-zeolite, activated carbon, and UV filtration can minimize the demand on clean water by 40-60%. The fiqh principle of reuse, assuming that water’s fundamental properties and volume (over two qullah or ~270 L) do not change, is pertinent here. The combination of these techniques confirms that ablution water reuse satisfies the green building water-efficiency objectives while also manifesting the Islamic principles of cleanliness (taharah) and moderation (wasatiyyah).